Catheter Ablation of Recurrent Paroxysmal Atrial Fibrillation: Is Gap‐Closure Combining Ganglionated Plexi Ablation More Effective?. Issue 6 (16th May 2017) - XU, FENG‐QIANG; YU, RONG‐HUI; GUO, JUN‐JIE; BAI, RONG; LIU, NIAN; AN, YI; GUO, XUE‐YUAN; TANG, RI‐BO; LONG, DE‐YONG; SANG, CAI‐HUA; DU, XIN; DONG, JIAN‐ZENG; et al.
Abstract : Background: For repeat treatment with paroxysmal atrial fibrillation (PAF) recurrence, gap‐closure at pulmonary vein ostia alone is not enough. Many recent studies indicated that ganglionated plexi (GPs) denervation could reduce the recurrence of AF. However, it is unclear whether the clinical outcomes of additional GP ablation plus pulmonary veins (PVs ) reisolation during a repeat procedure were associated with less recurrence in PAF patients. The purpose of this study was to evaluate if a repeat procedure of GP ablation (GPA) combining repeated procedure of pulmonary vein isolation (re‐PVI), i.e., gap‐closure, can offer additional benefit for patients with PAF recurrence. Method: A total of 123 consecutive patients with PAF recurrence who underwent success repeat procedures were retrospectively analyzed in our center (2014–2015). Note that 64 patients (group 1, GPA group) were performed with GPA plus re‐PVI, while 59 patients (group 2, re‐PVI group) had re‐PVI (gap‐closure) alone. Organized atrial tachycardias (OATs) documented or induced at the end of the procedure were all mapped and ablated. Patients were scheduled for a 12‐month follow‐up. Clinical presentation and outcome data for the two groups were assessed. Result: At the 12‐month follow‐up 58 of 64 patients (90.6%) in group 1 and 46 of 59 patients (78%) in group 2 remained in sinus rhythm (SR) off antiarrhythmia drugs (AADs) (P = 0.045). Conclusion: GPA conferred incremental benefit when performed in addition to re‐PVI in patients with PAF recurrence; the GPA group yielded higher success rates than the re‐PVI group.